Peran Masyarakat Dalam Pengembangan Daerah Wisata Tukad Bindu Kota Denpasar - Oka Prajanata I Nyoman; Nyoman Diah Utari Dewi; Ida Ayu Putu Sri Widnyani (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2024)
The development of the tourism industry makes the Denpasar City Government need innovation in finding tourism potential and increasing the number of tourist visits, but in its development, Tukad Bindu tourism objects have not fully become a superior tourist attraction. This can be seen from the lack of maintenance and maintenance of existing facilities and the number of people who do not maintain the cleanliness of Tukad Bindu. The purpose of this study is to determine the participation of the community in maintaining and managing Tukad Bindu tourism objects and the impact on the community on the existence of this tourist attraction. The method used is a qualitative approach, using secondary data sources and data collection techniques for literature studies and documentation. The results obtained include: first, the community's efforts in managing Tukad Bindu are reflected in the establishment of the Tukad Bindu Foundation. This foundation was originally a community that was later formed legally. Until now the Tukad Bindu Foundation has collaborated with various Regional Apparatus Organizations Denpasar City, Universities in Bali and river communities throughout Indonesia. In addition to aiming to preserve the river, the construction of Tukad Bindu is also to provide education to the community related to Community Based Tourism, namely community-based tourism. Second, the existence of Tukad Bindu tourism objects has an impact on the economy, social, and environment of the surrounding community.